2021
DOI: 10.1159/000517344
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte-to-Monocyte Ratio Is a Predictive Biomarker of Response to Treatment with Nivolumab for Gastric Cancer

Abstract: <b><i>Introduction:</i></b> Patients with unresectable or recurrent gastric cancer who have an objective response (OR) to nivolumab monotherapy are expected to have a good long-term prognosis. However, the OR rate for nivolumab treatment is low at 11%, and there is a need for biomarkers to predict the treatment response. This study aimed to analyze the significance of systemic inflammation-related variables and clinicopathologic characteristics as predictive markers of response to nivol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…35 Notably, LMR has shown predictive potential for immune checkpoint inhibitor effectiveness in various cancer types, including melanoma, non-small cell lung cancer, and gastric cancer. [50][51][52] Though we did not observe any association between the LMR and OS or PFS, we still believe LMRs to be valuable research directions.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…35 Notably, LMR has shown predictive potential for immune checkpoint inhibitor effectiveness in various cancer types, including melanoma, non-small cell lung cancer, and gastric cancer. [50][51][52] Though we did not observe any association between the LMR and OS or PFS, we still believe LMRs to be valuable research directions.…”
Section: Discussionmentioning
confidence: 58%
“…Therefore, lower LMR may reflect weaker regional immunity and the presence of an inflammatory state, promoting tumor growth within the microenvironment 35 . Notably, LMR has shown predictive potential for immune checkpoint inhibitor effectiveness in various cancer types, including melanoma, non‐small cell lung cancer, and gastric cancer 50–52 . Though we did not observe any association between the LMR and OS or PFS, we still believe LMRs to be valuable research directions.…”
Section: Discussionmentioning
confidence: 67%
“…In a multicenter study involving 200 patients treated with third-line nivolumab, the presence of LM was prognostic for PFS in both univariate (HR, 1.55; 95% CI, 1.12–2.14; P=0.008) and multivariate (HR, 2.01; 95% CI, 1.40–2.89; P<0.001) analyses. Similarly, Tokumaru et al [ 29 ] observed significantly worse PFS rates among patients with LM treated with nivolumab than among other patients (1-year PFS: 0.0 vs. 24.4%, respectively; P=0.005). The results obtained in our study are inconsistent with published data for OS, and our data showed that the presence of LM was not prognostic for OS (HR, 1.13; 95% CI, 0.95–1.35; P=0.1575), but it was for PFS (HR, 1.36; 95% CI, 1.15–1.61; P=0.0003).…”
Section: Discussionmentioning
confidence: 82%
“…Notably, two of the eligible articles ( 19 , 20 ) included two cohort studies respectively, resulting in a total of eight cohort studies. Among them, seven cohort studies were retrospective ( 19 , 20 , 24 , 26 , 27 ), whereas the remaining one was prospective ( 25 ). All cohort studies were published in English and released between 2021 and 2022.…”
Section: Resultsmentioning
confidence: 99%